Mapping the land cover dynamics of the Moanda Mangrove Marine Park in Central Kongo Province, DRC from 2002 to 2020 - Joël Tungi-Tungi Luzolo; Christ Lendo Masivi; Pacifique Madibi Mubamba; Michel Ngoy Kibwila; Jules Mitashi Kimvula (Pirineos: Revista de Ecología de Montaña)
The mangrove land cover is undergoing unprecedented anthropization. The main objective of this study is to map and quantify the dynamics of land cover in the Moanda Mangrove Marine Park between 2002 and 2020. Specifically, it aims to: (i) assess the annual rate of change in the mangrove land cover; (ii) estimate the influence of wood energy on the decline in mangrove forest area; and (iii) propose measures for the sustainable management of the Mangrove Marine Park forest. The study method is a combination of field survey, diachronic analysis of Landsat images and statistical analysis. The very good correspondence between the classification results and field reality was justified by the Kappa value (0.81) and overall accuracy (82.4%). The diachronic analysis of satellite images showed the regression of areas covered by forest classes in favor of the anthropogenic activities, herbaceous mangroves and the savannah. The annual deforestation rate in the Moanda Mangrove Marine Park is estimated at around 0.07%. The result points to the heavy dependence of coastal households in Moanda on fishing (31%), agriculture (26%) and charcoal production (22%), all of which put pressure on the natural resources of the Mangrove Marine Park. Promoting an integrated approach and techniques for the sustainable use of natural resources is an effective way of combating deforestation in the Moanda Mangrove Marine Park.